Monitoring System with Certified and Non-Certified Device Comparison - mazlan, afiq aiman; Hairulazwan Hashim (Progress in Engineering Application and Technology, 2024)
The "Monitoring System with Certified and Non-Certified Device Comparison" project aims to improve energy efficiency using IoT technology and SMATRUL WiFi Power Meters. It measures and compares energy consumption between certified and non-certified electrical appliances. Installed in the distribution box, these power meters monitor voltage, current, and power usage, transmitting data via WiFi to the Life app for real-time analysis. Results show significant differences in energy consumption, highlighting the benefits of energy efficiency certifications for consumers to manage their energy use effectively.